Progress of nursing interventions on malnutrition among patients with lung cancer (肺癌患者营养不良的护理干预研究进展) - ZHOU Yan (周艳); YUAN Ting (袁婷); FENG Juan (冯娟); YANG Zhen (杨珍) (中西医结合护理)
Malnutrition is a common cancer treatment side effect, leading to the decreased treatment tolerance and increased risk of complications induced by chemotherapy and radiotherapy. This paper summarized the studies on malnutrition among patients with lung cancer in perspectives of risk factors, evaluation tools and nursing interventions, in order to provide reference for clinical practice of lung cancer treatment and nursing. (营养不良是肺癌患者常见症状。营养不良可导致患者治疗耐受性下降、放化疗不良反应风险增加, 严重影响肺癌患者生活质量。本文从肺癌患者营养不良发生的危险因素、评估工具、护理干预措施等方面进行综述, 以期为临床护理人员选择合适的评估工具、给予有效的护理干预措施提供参考依据。)